Programa computacional para análise e verificação de seções de concreto armado e protendido com flexão oblíqua composta - Silva, Leonardo Martins e (2015)
In this paper, a free analysis program is presented for the verification of ultimate and serviceability limit states of reinforced or prestressed concrete sections with polygonal shape submitted to axial forces and biaxial bending. In addition, the program also calculates the bending-axial force-curvature relation (M, N, 1 / r) of the sections, which can be used in further analysis, for example, the general method for calculating pillars. For this is used the object-oriented programming, so that this work can be resumed and amended, providing technical material for future work in the same line, therefore provides that the calculation routines along with the program. The programming lines and routines includes explanations of its operation to encourage its further use as part of other programs. The data entry is presented as a form and the program enables the exchange of data, both input and output via text type files. The criteria adopted follows the brazilian standard ABNT NBR 6118: 2014, which compared to the previous version features suggestions for concrete with superior characteristic strength higher than 50 MPa. The structure of the routines is presented so that criteria of other standards, or updates of the same Brazilian standard referenced, can be easily implemented. Some validation examples for the program are presented in different situations and finally commented and listed some other extensions which can be made.